CLINICAL ASPECT OF NORMAL PRESSURE HYDROCEPHALUS: WHAT TO DO? A LITERATURE REVIEW - Nazwar, Tommy; Bal’afif, Farhad; Wardhana, Donny; Riskiyana, Riskiyana; Agustina, Kartika; Panjaitan, Christin (MNJ (Malang Neurology Journal), 2025)
Normal pressure hydrocephalus (NPH) is a medical condition characterized by the enlargement of brain ventricles and associated clinical manifestations, including gait disturbance, cognitive impairment, and urinary incontinence. In many cases, NPH is often misdiagnosed or diagnosed late due to its symptoms closely resembling those seen in other neurological conditions. Therefore, a comprehensive understanding of the clinical characteristics of NPH is crucial. This article aims to present an in-depth literature review on the clinical aspects of NPH and offer valuable insights to clinicians regarding the appropriate approach to diagnosing and managing patients with NPH. Gait apraxia is usually the first symptom, followed by incontinence and cognitive impairment, particularly in attention and memory. The diagnosis of NPH follows specific criteria, classifying patients as "possible" or "probable." Imaging examinations, such as computed tomography (CT) scans and magnetic resonance imaging (MRI), are essential to assess ventricular size and identify radiological findings such as ventriculomegaly, disproportionately enlarged subarachnoid space hydrocephalus (DESH), callosal angle, temporal cornu enlargement, and white matter changes. NPH can be managed through conservative care, ventriculoperitoneal (VP) shunt surgery, and, in select cases, endoscopic third ventriculostomy (ETV). VP shunt surgery is the main surgical option, offering different valve choices such as fixed-pressure, programmable-pressure, and overdrainage prevention mechanisms. VP shunts have been shown to effectively relieve NPH symptoms, with lumbo-peritoneal (LP) shunts considered less favorable due to higher complications. ETV is a possibility for specific patients.